The Effect of Storage Time of Fresh Human Amniotic Membrane on the Levels of Growth Factors Epidermal Growth Factor, Transforming Growth Factor Beta, and Basic Fibroblast Growth Factor in Freeze-dried Human Amniotic Membrane after Gamma Ray Irradiation - Ida Bagus Nyoman Ananta Awatara; Yuanita Safitri Dianti; Sitti Rizaliyana; Vijayendran Swaminathan (Biomolecular and Health Science Journal)
Introduction: The fresh amnion membrane is a popular option for wound healing. After cryopreservation, fibroblasts and epithelial cells in the amnion membrane remain viable, but their viability decreases when the membrane is freeze dried. This study focuses on how the storage time of gamma-irradiated freeze-dried human amniotic membrane impacts the levels of important growth factors for wound healing: epidermal growth factor (EGF), transforming growth factor beta (TGF-β), and basic fibroblast growth factor (bFGF). Methods: This was a post-test group experimental design, in which we used enzyme-linked immunosorbent assay tests to measure three growth factor (EGF, TGF-β, bFGF) levels in gamma-irradiated, freeze-dried human amnion membrane derived from three storage groups of fresh human amnion membrane (1 week, 3 months, and 9 months). Results: The 1-week storage group, EGF levels were too low to detect. However, at 3 months, the levels rose to 3.393 pg/mL, and at 9 months, they reached 6.503 pg/mL. Statistical analysis (Mann–Whitney test) showed no significant difference between the 3-month and 9-month groups (P = 0.689). For bFGF, levels were 61.396 pg/mL at 1 week, 36.005 pg/mL at 3 months, and 132.233 pg/mL at 9 months, with no significant differences across groups (P = 0.134). TGF-β levels were 17.469 pg/mL for 1 week, 34.812 pg/mL for 3 months, and 35.449 pg/mL for 9 months, again showing no significant changes (P = 0.069). Conclusion: The study found no significant differences in the levels of EGF, TGF-β, and bFGF in gamma-irradiated freeze-dried human amnion membrane after storage periods of 1 week, 3 months, and 9 months, suggesting that the storage duration does not adversely affect these growth factors. This could have implications for the use of amnion membranes in clinical settings.